Lung cancer : principles and practice - Mitchell, James B.; Pass, Harvey I. (Philadelphia : Lippincott Williams & Wilkins, 2000)
A comprehensive review of lung cancer, from screening, early detection, and prevention, to management strategies including surgery, chemotherapy, radiation therapy, and multimodality therapy, as well as novel therapeutic strategies, palliation and special considerations, and other thoracic tumors--Provided by publisher.
Etiology and epidemiology -- Lung cancer biology -- Screening/early detection/prevention -- Pathology and molecular classification -- Clinical presentation, diagnosis, staging, and prognosis -- Surgery -- Radiation therapy -- Chemotherapy -- Multimodallity therapy of NSCLC -- Treatment of small cell lung cancer -- Novel therapeutic strategies -- Palliation and special considerations -- Other thoracic tumors.
Includes bibliographical references and index.
Keywords: Lung Neoplasms